Impact of glaucoma and glaucoma surgery on quality of life - V.P. Erichev; A.V. Volzhanin (РМЖ "Клиническая офтальмология")
V.P. Erichev, A.V. Volzhanin Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Glaucoma is a chronic, incurable disease managed by controlling intraocular pressure (IOP). Meanwhile, vision loss in glaucoma and treatments affect the quality of life (QoL). Many studies on QoL in patients with glaucoma are now available. Standardized questionnaires and established non-linear relationships between QoL in glaucoma and clinically assessed quantitative parameters (e.g., visual acuity, visual fields, etc.) are significant achievements. Although treatments (pharmacotherapy or surgical interventions) generally reduce IOP, their adverse reactions affect QoL and treatment adherence. Surgical interventions provide the most potent IOP-lowering effect. However, surgery most affects QoL due to local symptoms and psychological factors (particularly at the early stages of glaucoma). Given the emergence of minimally invasive procedures, the importance of studying de facto QoL after glaucoma surgery is resurrected. Keywords: quality of life, glaucoma, trabeculectomy,  minimally invasive glaucoma surgery, neuroprotective therapy. For citation: Erichev V.P., Volzhanin A.V. Impact of glaucoma and glaucoma surgery on quality of life. Russian Journal of Clinical Ophthalmology. 2022;22(1):44–50 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-44-50.